Integrated omics analysis reveals the epigenetic mechanism of visceral hypersensitivity in IBS-D - Lu, Yaoyao; Chai, Yuna; Qiu, Jianli; Zhang, Jingmin; Wu, Menglin; Fu, Zhe; Wang, Yongfu; Qin, Chongzhen (Frontiers in Pharmacology, 2023)
Background and objective: IBS-D is a common functional bowel disease with complex etiology and without biomarker. The pathological and physiological basis of IBS-D focuses on visceral hypersensitivity. However, its epigenetic mechanism remains elusive. Our study aimed to integrate the relationship between differentially expressed miRNAs, mRNAs and proteins in IBS-D patients in order to reveal epigenetic mechanism of visceral hypersensitivity from transcription and protein levels and provide the molecular basis for discovering biomarkers of IBS-D. Methods: The intestinal biopsies from IBS-D patients and healthy volunteers were obtained for high-throughput sequencing of miRNAs and mRNAs. The differential miRNAs were selected and verified by q-PCR experiment followed by target mRNA prediction. Biological functions were respectively analyzed for target mRNAs, differential mRNAs and the previously identified differential proteins in order to explore the characteristic involved visceral hypersensitivity. At last, interaction analysis of miRNAs, mRNAs and proteins was performed for the epigenetic regulation mechanism from transcription and protein levels. Results: Thirty-three miRNAs were found to be differentially expressed in IBS-D and five of them were further confirmed, including up-regulated hsa-miR-641, hsa-miR-1843, hsa-let-7d-3p and down-regulated hsa-miR-219a-5p, hsa-miR-19b-1-5p. In addition, 3812 differential mRNAs were identified. Thirty intersecting molecules were found from the analysis on the target mRNAs of miRNAs and mRNAs. Fourteen intersecting molecules were obtained from the analysis on the target mRNAs and proteins, and thirty-six intersecting molecules were identified from analysis on the proteins and different mRNAs. According to the integrated analysis of miRNA-mRNA-protein, we noticed two new molecules COPS2 regulated by hsa-miR-19b-1-5p and MARCKS regulated by hsa-miR-641. Meanwhile some critical signaling pathways in IBS-D were found such as MAPK, GABAergic synapse, Glutamatergic synapse and Adherens junction. Conclusions: The expressions of hsa-miR-641, hsa-miR-1843, hsa-let-7d-3p, hsa-miR-219a-5p and hsa-miR-19b-1-5p in the intestinal tissues of IBS-D patients were significantly different. Moreover, they could regulate a variety of molecules and signaling pathways, which were involved in the multifaceted and multilevel mechanism of visceral hypersensitivity of IBS-D.